Answer:
A. y = -x + 1
Explanation:
First find the slope of the two lines using the slope formula:
.
![(2-(-2))/(-1-3) =(4)/(-4) =-1](https://img.qammunity.org/2020/formulas/mathematics/middle-school/c4zu6w0umyfmyb2x7txo2kjfxskjiejf2l.png)
Now use one of the two points; I am going to use (-1, 2).
Substitute the point and slope into the point-slope equation: y - y1 = m(x - x1).
y - (2) = -1(x - (-1))
Simplify.
y - 2 = -1x - 1
Add 2 to both sides and remove the 1 in front of the x. It is not needed.
y = -x + 1